ACUTE RESPONSE OF HIGH INTENSITY AEROBIC INTERVAL EXERCISE (HIIT) IN BLOOD PRESSURE OF HYPERTENSIVE OLDER WOMEN - Lourenço, Wilker; Sá Filho, Alberto Souza (International Journal of Movement Science and Rehabilitation, 2020)
Systemic arterial hypertension is a public health problem that affects most elderly adults. As a non-drug treatment moderate aerobic exercise shows reductions in elevated SBP, which is known as post-exercise hypotension. However, we do not know if high intensity interval aerobic exercise (HIIT). Objective: To analyze the hypotensive response of an HIIT exercise session in elderly hypertensive women. This is a cross-sectional experimental study of elderly hypertensive women aged ≥60 years. A questionnaire containing 17 questions was applied to identify and describe the sample. Only one visit to the laboratory was required, where BP was measured after 10 minutes sitting at rest. Soon after, the 17.5-minute HIIT session was applied and BP was measured again at time 0 (immediately), 10.20 and 30 minutes. The sample consisted of 10 women with a mean age of 70.2 ± 6.4 years. After exercise, SBP significantly decreased after 20 to 30 min post exercise (p <0.05). DBP showed distinct behavior rising slightly, tending to fall after 20 min of exercise. An HIIT session provided a reduction in SBP compared to the resting (pre) moment and could provide improvement in blood pressure control and possible reductions in the incidence of cardiovascular events.